Cardiovascular risk factors in patients with rheumatoid arthritis in combination with hypertension depending on body weight. - O. Yu. Sіrenko (Medičnì Perspektivi, 2014)
The objective was to evaluate the frequency of cardiovascular risk factors and hypertension in patients with rheumatoid arthritis depending on body weight. The study involved 100 patients with rheumatoid arthritis and stably selected therapy for more than 6 months at the age from 45 to 65 years (mean age 53,19 ± 5,40 years). Traditional cardiovascular risk was assessed, taking into account risk factors by SCORE scale and amended for patients with RA. The levels of total cholesterol, triglycerides, C-reactive protein, serum creatinine, body mass index, body area index were determined. Arterial hypertension was diagnosed in 41 (41%) patients with rheumatoid arthritis and was associated with traditional risk factors (age, obesity), rheumatoid factor, hyperuricemia and the duration of glucocorticoid therapy. Obesity and excess body mass occurred in the majority of patients with rheumatoid arthritis, herewith the highest level of inflammation indicators and risk of cardiovascular events was in overweight patients. Obesity was associated with duration of rheumatoid arthritis, the activity of the inflammatory process, the duration of glucocorticoids taking. It is found that the traditional SCORE scale does not fully reflect the risk of cardiovascular events in rheumatoid arthritis. Identification of hypertension and obesity increases the information content of the risk assessment of cardiovascular events in rheumatoid arthritis.